Elevated serum Dickkopf-1 is a biomarker for bone erosion in patients with psoriatic arthritis. Issue 21 (5th November 2021) - Chung, Yukchiu; Li, Zhi-Chang; Sun, Xiao-Lin; Liu, Yan-Ying; Shao, Miao; Gan, Yu-Zhou; Li, Yi-Min; Li, Yu-Hui; Zhang, Xue-Wu
Abstract: Background: Psoriatic arthritis (PsA) is an inflammatory arthropathy characterized by psoriasis and bone erosion on radiology. Dickkopf-1 (Dkk-1) is considered to be the main inhibitor of the Wnt signaling pathway and results in reduced osteoblast proliferation. The aim of this study was to investigate the serum level of Dkk-1 and its association with bone erosion in PsA patients. Methods: Serum Dkk-1 levels were measured by enzyme-linked immunosorbent assay (ELISA) in 69 patients with PsA and 60 controls, including 39 rheumatoid arthritis (RA) patients, and 21 healthy controls (HCs). Rheumatoid factor and anti-cyclic citrullinated peptide levels were also determined by ELISA. The association of Dkk-1 level with clinical and laboratory features of PsA was analyzed. Logistic regression analysis was used to analyze the risk factors for bone erosion in PsA. Results: Dkk-1 was elevated in 68.1% (47/69) of the patients with PsA, 46.2% (18/39) of RA patients, and 9.5% (2/21) of HCs. Serum Dkk-1 concentration was significantly higher in PsA patients compared with that in HCs. The level of serum Dkk-1 was correlated with a swollen joint count, and levels of complement components 3 and 4. Elevated Dkk-1 level (odds ratio = 4.440, 95% confidence interval: 1.246–15.817, P  = 0.021) was identified as the risk factor for bone erosion in PsA. Conclusions: The serum level of Dkk-1 is abnormally elevated in PsA patients. The elevation of Dkk-1 might be involved in the mechanism of bone erosion in patients with PsA.